Peak Amplitude Transmission on High-Rise Structure by Implementing TMD Method - Salim, Mohd Azli; Putra, Azma; ABDULLAH, Mohd Azman; Noordin, Aminurrashid; Tee, Boon Tuan (American Scientific Publishers, 2013)
This research is to gain an understanding and developed a test-rig for high-rise structure isolation for ground motion in vibration and noise phenomenon in ASEAN Region especially the place has a huge earthquake. In this study, a 7-storey high rise building designed by 1:20 scale with actual design has been developed. There are three types of simply structure base which is a pure force, rigid body and short resonant beam. These bases are connected to the ground structure of building via a single isolator. The outcome of this study is expressed the frequency averaging energy transmission and peak amplitude transmission to the ground structure motion in terms of approximate source and isolator mobility formulae. A theoretical prediction is compared with experimental measurements. It is useful to predict an energy transmission from ground motion of a structure, more profound understanding and greater confidence on the approach is gained unless measurements can made. The methods called frequency domain acceleration data and structural frequency response information is used in this study. These methods are chosen because there is energy input to the structure at a single isolator, and then the energy is transmitted through an isolator using acceleration at the top and bottom. The energy then absorbed by finite resonant structure using accelerations at one, two and four points. By right, after completed this study and experiment, the response on ground isolator of high-rise structure can be understood in depth.